2017
DOI: 10.1016/j.bbr.2017.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic stress during adolescence in prefrontal cortex structure and function

Abstract: h i g h l i g h t s• Chronic stress impairs the development of the adolescent brain.• Chronic stress delays the maturation of extracellular structures called perineuronal nets, which stabilize synaptic contacts on inhibitory neurons, and prefrontal cortex-associated behavior.• These negative effects of chronic stress on the prefrontal cortex can theoretically occur in humans. Critical periods of plasticity (CPPs) are defined by developmental intervals wherein neuronal circuits are most susceptible to environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 82 publications
3
16
0
Order By: Relevance
“…Human postmortem studies revealed marked abnormalities of aggrecan and PV-expressing neurons in schizophrenia and bipolar disorder (Pantazopoulos et al, 2015;Steullet et al, 2018). Preclinical studies also showed that early life stress or chronic stress during adulthood altered PNN numbers in multiple brain regions including prefrontal cortex (Castillo-Gómez et al, 2017;de Araújo Costa Folha et al, 2017;Pesarico et al, 2019). The PNN assembly and its molecular components may play a critical role in stress response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human postmortem studies revealed marked abnormalities of aggrecan and PV-expressing neurons in schizophrenia and bipolar disorder (Pantazopoulos et al, 2015;Steullet et al, 2018). Preclinical studies also showed that early life stress or chronic stress during adulthood altered PNN numbers in multiple brain regions including prefrontal cortex (Castillo-Gómez et al, 2017;de Araújo Costa Folha et al, 2017;Pesarico et al, 2019). The PNN assembly and its molecular components may play a critical role in stress response.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have implicated the alterations in the density or composition of PNNs in a range of neuropsychiatric disorders such as epilepsy (Tewari et al, 2018), schizophrenia (Bitanihirwe and Woo, 2014;Enwright et al, 2016), bipolar disorder (Steullet et al, 2018), and drug addiction (Xue et al, 2014;Blacktop and Sorg, 2019), and these behavioral abnormalities might be improved after reversing the changes in the number of components of PNNs. Chronic stress during early life or adulthood alters the density of PNNs in the medial prefrontal cortex, and affects the structure and plasticity of inhibitory neurons, especially PV-expressing interneurons (Castillo-Gómez et al, 2017;de Araújo Costa Folha et al, 2017;Pesarico et al, 2019). Early life maltreatment or maternal immune activation caused developmental abnormalities in PNNs in the prefrontal cortex and basolateral amygdala (Paylor et al, 2016;Page and Coutellier, 2018;Santiago et al, 2018), which may be associated with the increased vulnerability to neuropsychiatric disorders such as anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…The lesions of the PFC can be caused by various reasons including trauma, surgical interventions, infections, toxins, chemicals, narcotic drugs, alcohol and chronic stress [32][33][34][35][36][37][38][39][40][41][42].…”
Section: Lesions Of the Prefrontal Cortexmentioning
confidence: 99%
“…Chronic stress slows down the maturation of PFC during the developmental period and affects its functions [40].…”
Section: Lesions Of the Prefrontal Cortexmentioning
confidence: 99%
“…The remarkable adaptability of the human brain results from the interplay of both evolutionary and developmental mechanisms. Genetically determined developmental programs set up the stage upon which cortical circuits are sculpted by experience and learning, particularly during the sensitive periods of synaptic plasticity [1][2][3]. The primary auditory cortex is structurally mature as early as 28 weeks of gestation [4] and already responds electrically to sounds in the low-frequency range associated with speech [5,6].…”
Section: Introductionmentioning
confidence: 99%